2010
DOI: 10.1111/j.1743-6109.2010.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity a Further Cardiovascular Risk Factor in Patients with Erectile Dysfunction?

Abstract: Introduction Erectile dysfunction (ED) and, in particular, arteriogenic ED have been proposed as new markers of risk for incident major adverse cardiovascular events (MACE). Reduced penile blood flow is more common in obese people than in leaner ED subjects. Aim To explore the interaction of overweight/obesity and penile blood flow in the prediction of incident MACE. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 69 publications
2
26
1
1
Order By: Relevance
“…We now originally report associations between WC and potential CV risk factors in a large series of subjects seeking medical care for ED at our unit (see above). We confirmed that also different WC grades, as previously reported for BMI classes,323 are associated with an increasing severity of hyperglycemia, insulin resistance and the prevalence of diabetes mellitus ( Figure 4a–c ) as well as dyslipidemia ( Figure 4d–f ). Similarly, pulse pressure, mean blood pressure and prevalence of hypertension were all closely related to WC increment ( Figure 5a–c ).…”
Section: Obesity Ed and CV Risksupporting
confidence: 91%
See 2 more Smart Citations
“…We now originally report associations between WC and potential CV risk factors in a large series of subjects seeking medical care for ED at our unit (see above). We confirmed that also different WC grades, as previously reported for BMI classes,323 are associated with an increasing severity of hyperglycemia, insulin resistance and the prevalence of diabetes mellitus ( Figure 4a–c ) as well as dyslipidemia ( Figure 4d–f ). Similarly, pulse pressure, mean blood pressure and prevalence of hypertension were all closely related to WC increment ( Figure 5a–c ).…”
Section: Obesity Ed and CV Risksupporting
confidence: 91%
“…However, the impact of obesity in ED subjects on the risk of incident CVD has been endorsed only by few studies,386 and the role of central obesity has never been explored. We now originally report associations between WC and potential CV risk factors in a large series of subjects seeking medical care for ED at our unit (see above).…”
Section: Obesity Ed and CV Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a recent large population-based study involving more than 3400 subjects from eight European centers (EMAS study) showed that about half of subjects were overweight or obese with an even higher prevalence in Eastern transitional countries (2). Excess body weight is a crucial risk factor for mortality and morbidity not only for cardiovascular diseases (CVD) but also for type 2 diabetes mellitus (T2DM), cancer, and musculoskeletal disorders; these complications cause nearly 3 million deaths every year worldwide (3,4,5,6,7,8). Despite this evidence, obesity is one of today's most blatantly visible -yet most neglected -public health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Besonders interessant sind auch die Aspekte zwischen erektiler Dysfunktion, Fettsucht und Hypogonadismus, wobei Corona et al [10] gezeigt haben, dass sowohl der "Body Mass Index" (BMI) wie auch der vergrößerte Bauchumfang mit reduzierten Testosteronspiegeln (Hypogonadismus) signifikant korrelieren. Darüber hinaus hat die gleiche Arbeitsgruppe [11] in einer Metaanalyse dargestellt, dass eine Testosterongabe die Symptome des metabolischen Syndroms signifikant verbessert (.…”
unclassified